Laparoscopic diagnosis of ascites in Lesotho. Issue 6493 (17th August 1985) - Menzies, R I; Fitzgerald, J M; Mulpeter, K
Abstract : In a prospective study of 98 consecutive patients with undiagnosed ascites examined by laparoscopy a correct immediate diagnosis was made in 76 (78%) and a final diagnosis in 92 (94%) of those who underwent laparoscopy. Visual diagnosis was highly accurate in patients with tuberculous peritonitis but only moderately accurate in those with carcinomatosis and liver disease. When the laparoscopic findings were compared with histological and microbiological results visual diagnosis was found to be the most accurate diagnostic method. Laparoscopy may readily be used in rural hospitals for diagnosing ascites.